PERANAN KEMAMPUAN KOMUNIKASI BAHASA INGGRIS GUNA PENINGKATAN DAYA SAING SDM MENGHADAPI MEA (MASYARAKAT EKONOMI ASEAN) - Sigit Widiyarto; Sri Sulastri (UNIVERSITAS INDRAPRASTA PGRI, 2015)
ASEAN as a single market-based production is supported by elements of the free flow of goods, services, investment, labor educated and free of capital flow. The Indonesian goods production will be fully compete with goods production ASEAN countries. So, then Indonesia must prepare all sectors, such as the human resource, specially English Communication Ability. The English Communication Ability (ECA) plays an important role in economic movement to rush national economic growth as well as global economic. The English Communication Ability absolutely must be planned continously by government and private company or corporation. At the first year of MEA (Asean Economic Community ) the movement of US Dollar was strong that can influence the foreign exchange. The government of Indonesia has maintained Rupiah currency and all sectors, including English Communication English Skill (ECA) Indonesian workers must have ECA well. Individuals may increase their own stock of per capita skills through formal and informal education. Further more, they will have well English Communication ability, then they would be able to have an higher income.